PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR PROPERTIES AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA 2019-2021 - Intan Tri Letiana; Ulil Hartono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
The establishment of a company is to gain profit. However, in reality the company is not immune from the threat of financial difficulties. Therefore, an analysis is needed to determine the factors that influence it. The variables in this study are profitability, liquidity, leverage and sales growth to predict companies experiencing financial distress. The sample in this study is 66 companies in the Properties and Real Estate sector which are listed on the Indonesia Stock Exchange 2019-2021. Using logistic regression analysis techniques, the results show that ROA has a negative effect on financial distress, because the higher the value of a company's ROA, the lower the probability that the company will experience financial distress. While CR, DAR and Sales Growth have no effect on financial distress, a high CR cannot free a company from financial distress. A low DAR also cannot be used as a predictor of a company experiencing financial distress. Increased sales growth cannot prevent the company from experiencing financial difficulties. So that CR, DAR and Sales growth are not consistent in explaining their probabilities with the condition of companies experiencing financial distress